Lifestyle Medicine Assessment Among The General Population Of District Sialkot, Pakistan: A Comparative Study - Mahwish, Rabiah; Liaquat, Fariha; Aslam, Imrana; Iqbal, Tariq (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the lifestyle medicine among the general population of the district of Sialkot, Pakistan. Methods: A comparative cross-sectional study was conducted in 4 Tehsils of District Sialkot, from April to September 2024. A calculated sample of 400 healthy individuals was selected by a non-probability consecutive sampling technique, and data were collected through a modified version of the lifestyle assessment short form questionnaire Results: The average age of participants was 33.58 ±13.06 years, with a predominant representation of males (60%). The majority of the respondents were young (93.5%) and graduates or post-graduates (55.4%). The mean lifestyle medicine score was 38±4.41. Only 40%of the participants had a favourable lifestyle medicine score above the mean. Education of the participants showed a significant association with lifestyle medicine score(p=0.027), while age, area of residence and social class revealed a non-significant association. Conclusion: Most of the study participants had unfavourable lifestyle medicine scores below mean indicating poorer adherence to recommended lifestyle medicine practices. Similarly for individual life style medicine domains, score was below the mean except for smoking and substance abuse domain.